PICKLED PRODUCTS FROM GREEN MUSSEL - MURALEEDHARAN, V; JOSEPH, K GEORGE; DEVADASAN, K (Fishery Technology, 2017)
Methods of preparing different types of delicious ready to serve pickled productsfrom green mussel (Perna viridis) and a comparative study of their storage characteristics are reported. Of the three types of products, namely, dried and pickled, fried and pickled and light smoked and pickled, the last one had the best shelf life. The optimum conditions of drying and smoking for preparing such type of pickles are also reported.